LPC envelope difference criterion and multiplexing efficiency - Shah, Asadullah; Dwi Handayani, Dini Oktarina (IIUM Press, 2011)
Linear Predictive Coding (LPC) envelop difference is a technique that exploits envelop of each frame. This is a frequency domain measure in which for each active speech frame and its reconstructed frame is used to find out the differences in their envelops. This LPC difference measures can be utilised for the STDM design purpose. This chapter is dedicated for LPC envelop as a frame discarding criterion to maximize the bandwidth